Law for Sustainable Development: Theoretical Perspectives and Implications for Law-Making in Vietnam - Anh, Nguyen Hoang (VNU Journal of Science: Legal Studies, 2026)
Sustainable development is not only a policy objective but must also be recognized as a guiding requirement for the legal system. In Vietnam, the understanding of sustainable development has unique characteristics that reflect Vietnam's specific context and therefore necessitate a re-examination of the role of law in harmonizing economic, social, and environmental goals in a long-term, integrated, and systematic manner. This article analyzes several theoretical issues concerning law for sustainable development, ranging from a sectoral to a principled, interdisciplinary approach; it also points out gaps in legal understanding and legal design in Vietnam today. The article argues that lawmaking for sustainable development needs to be situated within a systems-thinking, constructive approach, with fundamental requirements such as balance, long-term perspective, consistency, feasibility, and social participation. From that perspective, the article proposes several directions to improve Vietnam's legal system and promote more effective, sustainable development.